The Influence of Trust, Health Beliefs, and Technology Acceptance on The Intent to use an Mhealth in Indonesia: An Empirical Study of Users and Non-Users - Sheila Amalia Salma; Ari Widyanti; Khoirul Muslim; Titis Wijayanto; Fitri Trapsilawati; Hilya Mudrika Arini; Adhi Dharma Wibawa (International Journal of Technology, 2024)
Mobile Health (mHealth) use is expected to promote public health and has been viewed as a possible solution for the management of the COVID-19 outbreak since 2020. However, the use of m-heath in those countries, including Indonesia, is not as expected, probably due to low acceptance and willingness to use mHealth. This study observed the influence of trust, health belief, and technology acceptance on the intention to use mHealth in Indonesia for both users and non-users. A total of 616 respondents, with a balanced number of users and non-users of mHealth, voluntarily participated in this study by filling out a questionnaire. The questionnaire was developed based on a conceptual model integrating trust, health belief model, and technology acceptance. A total of 34 questions were administered based on the conceptual model. A five-Likert scale was used to measure the answers. Interesting findings showed that among the non-users of mHealth, perceived usefulness influenced the intention to use mHealth more than that among those who actually used the technology. Among the users of mHealth, perceived ease of use influenced the intention to use the technology more than that among the non-users. The effect of trust was not shown to be significant. In general, intention to use mHealth in Indonesia was significantly influenced by perceived usefulness, perceived ease of use, and perceived health risk.